Comparison between MCQ, Extended matching questions (EMQ) and Script concordance test (SCT) for assessment among first-year medical students - A pilot study - YC Nalini; Shivashakthy Manivasakan; Dinker R. Pai (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Single-best response types of MCQs are commonly used tools in medical assessment. However, these are not particularly apt for the assessment of higher-order thinking skills (HOTS) among students. Assessment of HOTS and clinical reasoning skills requires unexplored tools like extended matching questions (EMQs) and SCTs. The aim is to assess HOTS and clinical reasoning skills during formative assessment among medical students post a simulation-based education (SBE) using EMQ and SCT on the topic of shock and collect student perceptions regarding new assessment tools. METHODS AND MATERIAL: The research is an observational descriptive study. Fifty-two first-year medical students were asked to take a formative assessment consisting of 20 MCQs, 6 EMQs, and 2 SCT post a SBE during July 2022 on the topic of shock. MCQs were categorized into themes of aetiology, pathophysiology, and management of shock. These categorized MCQs were compared and analyzed with EMQs and SCTs prepared on the same themes. The data analysis by a one-way analysis of variance (ANOVA) was conducted to compare the difference in per cent mean scores of MCQ with EMQ and MCQ with SCT. RESULTS: The overall mean scores and also under the theme of aetiology and management, the student's score in MCQ were higher than EMQ and SCT and the difference was statistically significant with the P value (≤0.001). CONCLUSIONS: Students scored better in familiar assessment tools like MCQ, but majority of the students were of the opinion that EMQ tested the delivered content better and SCT tested the clinical application better.